PERAN KEPALA SEKOLAH SEBAGAI MANAGER PENDIDIKAN DI PAUD KASIH EFRATA JATIASIH BEKASI - Julinda Siregar (Universitas Darunnajah, 2023)
Abstract. The Role of the School Principle as an Education Manager in PAUD Kasih Efrata Jatiasih Bekasi. This study aims to get an empirical picture of the ability of the Principal in: 1) Planning a work program, 2) Organizing the duties and responsibilities of teachers, 3) Implementing a work program, 4) Carrying out an assessment of teacher work, 5) Carrying out an evaluation of the results of the teacher's work, and 6) Supporting the activities of the teachers. This research uses a descriptive method. Informants in this study are the principal and teachers. The location of the research was in PAUD Kasih Efrata Jatiasih Bekasi. Data was collected through in-depth interviews, observation and documentation. The data analysis techniques through data reduction and data verification. The results of the study show that: 1) the principal has a role in managing teacher activity programs, 2) the principal carries out activities to provide information to teachers starting from what time the teacher can leave school to provide full support to teachers in carrying out their duties at school, 4) the principal in assessing the activities of the teachers, the activities of the teachers are properly monitored, 5) the principal in carrying out inference activities on the results of the teacher's activities, 6) the principal improves learning facilities and facilities needed by students in accordance with the needs of students such as classrooms, play equipment both inside and outside the classroom.